A metatranscriptomic evaluation of viruses in field-collected bed bugs - Sheele, Johnathan M; Peta, Vincent; Miron, Alexander; Balvin, Ondrej; Cain, David; Edelheit, Simone; McCormick, Tom; Pietri, Jose E (Parasitology research, 2023)
Cimex lectularius, known as the common bed bug, is a widespread hematophagous human ectoparasite and urban pest that is not known to be a vector of any human infectious disease agents. However, few studies in the era of molecular biology have profiled the microorganisms harbored by field populations of bed bugs. The objective of this study was to examine the viruses present in a large sampling of common bed bugs and related bat bugs (Cimex pipistrelle). RNA sequencing was undertaken on an international sampling of > 500 field-collected bugs, and multiple workflows were used to assemble contigs and query these against reference nucleotide databases to identify viral genomes. Shuangao bed bug virus 2, an uncharacterized rhabdovirus previously discovered in Cimex hemipterus from China, was found in several bed bug pools from the USA and Europe, as well as in C. pipistrelle, suggesting that this virus is common among bed bug populations. In addition, Shuangao bed bug virus 1 was detected in a bed bug pool from China, and sequences matching Enterobacteria phage P7 were found in all bed bug pools, indicating the ubiquitous presence of phage-derived elements in the genome of the bed bug or its enterobacterial symbiont. However, viral diversity was low in bed bugs in our study, as no other viral genomes were detected with significant coverage. These results provide evidence against frequent virus infection in bed bugs. Nonetheless, our investigation had several important limitations, and additional studies should be conducted to better understand the prevalence and composition of viruses in bed bugs. Most notably, our study largely focused on insects from urban areas in industrialized nations, thus likely missing infrequent virus infections and those that could occur in rural or tropical environments or developing nations.
Keywords: Animals; Viruses; Arbovirus; Virus; Europe; štěnice; China; RNAseq; Bed bug; Metatranscriptomics; viry; lidé; infestace ektoparazity; Ectoparasitic Infestations; Evropa; Bedbugs; Cimex lectularius; Čína; zvířata; Cimex pipistrelle; Humans